1990
DOI: 10.1002/cjce.5450680101
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional turbulent flow in agitated vessels with a nonisotropic viscosity turbulence model

Abstract: Solutions of the time‐averaged equations of motion with a nonisotropic k‐e model were developed for the three‐dimensional turbulent flow field in turbine stirred tanks. These results were validated with the measurements of three velocity components with a hot wire anemometer and literature data. The nonisotropic turbulence model considered the rotation and curvature effect of the turbulence with a turbulent Richardson number term and accounted for the important three‐dimensional effects through the nonisotropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Applying the experimental investigation of Ståhl Wernersson [5] to estimate the kinetic energy at the centerline of the turbine (Eq. (5)), one can note that the numerical results of Ju et al [63] are in good agreement with experimental data (Tab. 1).…”
Section: Fluid Dynamic Approach: Cfd Modelssupporting
confidence: 85%
See 2 more Smart Citations
“…Applying the experimental investigation of Ståhl Wernersson [5] to estimate the kinetic energy at the centerline of the turbine (Eq. (5)), one can note that the numerical results of Ju et al [63] are in good agreement with experimental data (Tab. 1).…”
Section: Fluid Dynamic Approach: Cfd Modelssupporting
confidence: 85%
“…Using the ke turbulence model, Lee et al [62] concluded their numerical investigation with the remark that improvements to the physical model were required in order to correctly predict the values of k near the impeller. With respect to anisotropy, Ju et al [63] employed a nonlinear k-e model and reported much better agreement with experimental results, both in the impeller and bulk regions for mean velocity components and fluctuation profiles. These authors also presented diagrams of simulated turbulent kinetic energy and contours of energy dissipation rates in a vertical plane of the stirred reactor.…”
Section: Fluid Dynamic Approach: Cfd Modelsmentioning
confidence: 69%
See 1 more Smart Citation
“…Ju et al [11] used a nonisotropic viscosity turbulence model. Kresta and Wood [2] and Ranade and Joshi [3] simulated the flow with the black box method and the k-e turbulence model.…”
Section: Mathematical Model and Simulation Methodsmentioning
confidence: 99%
“…In some of these simulations, the flow in and out, L S and ε, were based on experimental data (Patterson, 1975;Mann and Knysh, 1984). It is now possible using standard CFD codes to numerically compute spatial distributions of Reynolds-averaged variables of the turbulent flow and mixing of miscible fluids with similar viscosities and densities in almost any geometry (see Hutchings et al, 1989;Bakker and van den Akker, 1990;Ju et al, 1990;Bakker and Fasano, 1993;Perng and Murthy, 1993;Dilber and Rosenblat, 1995;Harvey et al, 1995;Fox, 1995;Armenante and Chou, 1996;Zipp and Patterson, 1998). Circulation patterns and distribution of turbulence intensities are generally good and predict the trends correctly, but the values of the turbulent quantities k and ε are not always correct.…”
Section: -57 Paired-interaction Closure For Multiple Chemical Reacmentioning
confidence: 99%